2007
DOI: 10.1210/en.2006-1479
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Microvesicles Secreted by 3T3-L1 Adipocytes: Redox- and Hormone-Dependent Induction of Milk Fat Globule-Epidermal Growth Factor 8-Associated Microvesicles

Abstract: Adipocytes are now recognized as endocrine cells secreting adipocytokines, regulating multiple metabolic pathways. In this study, we addressed secretion of microvesicles by 3T3-L1 adipocytes. We found that MFG-E8, one of the exosomal proteins, was present in the microvesicles and was distributed in the sucrose density fractions with 1.13-1.20 g/ml, which has been reported for exosomes. Several integral, cytosolic, and nuclear proteins such as caveolin-1, c-Src kinase, and heat shock protein 70 were also found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 63 publications
6
130
0
2
Order By: Relevance
“…Moreover, the signature of circulating miRNAs changed concomitantly with extensive weight loss. Interestingly, recent studies have demonstrated that adipocytes secrete microvesicles that may contain oligonucleotides (40 ). Indeed, adipocyte/adipose tissue-specific gene transcripts and microRNAs were found in microvesicles isolated from rat serum (13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the signature of circulating miRNAs changed concomitantly with extensive weight loss. Interestingly, recent studies have demonstrated that adipocytes secrete microvesicles that may contain oligonucleotides (40 ). Indeed, adipocyte/adipose tissue-specific gene transcripts and microRNAs were found in microvesicles isolated from rat serum (13 ).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of PREF-1, a negative regulator of adipogenesis, decreased in EVs derived from cells during the later stages of differentiation (Connolly et al, 2015). Other adipogenesis-related proteins were also detected in adipocyte-derived exosomes including adenylate kinase 2 (AK2), and matrix metalloproteinase-2 and -9 (MMP-2 and MMP-9) (Lee et al, 2015;Aoki et al, 2007). Furthermore, mRNAs encoding the adipogenesis-related proteins PPARγ, leptin, C/EBP-α and C/EBP-δ have also been detected in adipocyte-derived EVs and as being delivered to osteoblasts (Martin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, fibroblast growth factor-1 is exported through an unconventional release pathway involving the formation of a specific multiprotein complex [63]. Furthermore, murine adipocytes release various proteins lacking a secretory signal sequence by microvesicles and, most interestingly, AFABP is detected in microvesicles [64]. These findings are supported by an independent study that [73] 98 CAD Associated with MS + TG [74] 479 with carotid IMT Associated with IMT in women + Age, BP, carotid IMT (in women) [75] 234 with coronary angiograms Associated with CAD n.d. [76] 211 CAD ↑ in CAD + CAD 211 controls [77] 125 CAD ↑ in CAD + Plaque volume (CAD) 120 controls [78] 247 CAD ↑ in CAD + Coronary atherosclerosis index 94 controls [79] 18 CAD/CVD ↑ in CVD n.d. 18 controls [80] 87 controls Associated with vascular inflammation + Vascular inflammation [90] 306 acute ischaemic stroke ↑ in ischaemic stroke n.d.…”
Section: Circulating Afabp-a Potential Novel Adipokinementioning
confidence: 99%